2022
DOI: 10.24106/kefdergi.910848
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Decision-Making Process In School Management

Abstract: Bu araştırmanın amacı; okul yöneticilerinin veriye dayalı karar verme kavramına ilişkin algılarını, veriye dayalı karar sürecinin işleyişi, bu sürece etki eden faktörleri ve sürecin iyileştirilmesine yönelik önerileri incelemektir. Nitel yöntemle gerçekleştirilen çalışmada olgu bilim deseni benimsenmiştir. Katılımcıların belirlenmesinde amaçlı örnekleme yöntemlerinden maksimum çeşitlilik ve ölçüt örnekleme teknikleri kullanılmıştır. Kahramanmaraş il merkezinde görev yapan 17 okul yöneticisi çalışma grubuna dâh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Armstrong and Anthes (2001) found that teachers have difficulty in mostly connecting them to a teaching strategy when using data. Whereas the fact that school principals and teachers have data literacy knowledge and skills play a role in making the decisions to be taken for the development of the school and student learning, based on data by making foresight and well-designed (Doğan, 2021). This study aims to apply the Turkish adaptation of the Data Literacy Scale (DLS), developed by Abrams et al (2021), and to test its validity and reliability.…”
Section: Extended Abstract Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Armstrong and Anthes (2001) found that teachers have difficulty in mostly connecting them to a teaching strategy when using data. Whereas the fact that school principals and teachers have data literacy knowledge and skills play a role in making the decisions to be taken for the development of the school and student learning, based on data by making foresight and well-designed (Doğan, 2021). This study aims to apply the Turkish adaptation of the Data Literacy Scale (DLS), developed by Abrams et al (2021), and to test its validity and reliability.…”
Section: Extended Abstract Introductionmentioning
confidence: 99%
“…Armstrong ve Anthes (2001) öğretmenlerin veri kullanırken en çok bir öğretim stratejisine bağlamakta zorlandıklarını tespit etmiştir. Oysaki okul yöneticisi ve öğretmenlerin veri okuryazarlığı bilgi ve becerilerine sahip olması, okulun gelişimi ve öğrenci öğrenmesi için alınacak kararların, öngörüsü yapılarak ve iyi tasarlanarak veriye dayalı alınmasında rol oynamaktadır (Doğan, 2021).…”
Section: Introductionunclassified